Diversity of Storage Insect Pests of Maize (Zea mays L.), their Damage and Losses Causes to Maize in Gabilay District, Somaliland - Barre, Jamaal; Jenber, Abaynew Jemal (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Maize is one of the foremost cereals cultivated today, and it is a queen of cereals. Maize is threatened by a wide range of post-harvest insect pests. Therefore, a survey was conducted in Gabilay District, Somaliland in 2021 to determine the status of storage pests. During the survey a total of 60 maize storage structures were assessed in three villages of Gabilay District namely; Galloley, Ijaara, and Boqor. Data on storage structures, infestation status, grain damage, and weight loss were collected and analyzed by SPPS version 20 and interpreted using descriptive statistics. The result showed that a locally constructed bit was the major storage structure followed by sacks while iron tank is used at the lowest level. Results found also indicated that all storage structures were infested by two major insect pests, i.e., Maize weevil (S. zeamais) and Angoumois grain moth (S. cerealella) at the highest level and by molds and rats to a lesser extent. Galloley site was infested only by maize weevil, while Boqor and Ijaara sites were infested by both maize weevil and angoumois grain moth. Maize weevil accounted for the lion's share of the infestation compared to angoumois grain moth. The highest grain damage was recorded at the bottom position of the storage structure from the Ijaara area followed by Galloley and Boqor. Likewise, grain weight loss was also highest at the bottom position that showed 12.0%. These findings provide benchmark information for developing sustainable management methods for the storage of insect pests of maize in the study area. It is also recommended training on storage methods, management of storage pests and healthy maize preparation should be practiced.